Evaluation of mechanical properties of dental feldsphatic porcelains for metal and zirconia core - de Almeida, Antonio Alves [UNESP]; Adabo, Gelson Luis [UNESP]; Galvao, Beatriz Regalado [UNESP]; Longhini, Diogo [UNESP]; dos Santos, Claudinei (Trans Tech Publications Ltd, 2012)
Studies has been reported a significant incidence of chipping of the feldspathic porcelain veneer in zirconia-based restorations. The purpose of this study was to compare the three-point flexural strength (MPa), Weibull parameters, Vickers hardness (VHN) and Vickers indentation fracture toughness (MPa/mm(1/2)) in feldspatic porcelains for metal and for zirconia frameworks. Bar specimens were made with the porcelains e.MaxCeram (EM) and VitaVM9 (V9) for zirconia core, and Duceragold (DG) and VitaVMK95 (VK) for metal core (n = 15). Kruskal-Wallis and Dun test were used for statistical analysis. There was no significant difference (p=0.31) among the porcelains in the flexural strength (Median = 73.2; 74.6; 74.5; 74.4). Weibull calculation presented highest reliability for VK (10.8) followed by em (7.1), V9 (5.7) and DG (5.6). Vickers hardness test showed that em (536.3), V9 (579.9) and VK (522.1) had no difference and DG (489.6) had the lowest value (p<.001). The highest fracture toughness was to VK (1.77), DG (1.58) had an intermediate value while V9 (1.33) and em (1.18) had the lowest values (p<.001). Despite of the suitable flexural strength, reliability and high hardness, the porcelains used to zirconia-based fixed dental prostheses showed lower fracture toughness values.
Keywords: dental ceramic; esthetics; zirconia; fixed prosthesis; veneering ceramics